Review of digital twin applications in manufacturing - Cimino, Chiara; Negri, Elisa; Fumagalli, Luca (Computers in industry, 2019)
•A deep literature review on DT applications in manufacturing is performed.•Rarely a DT environment offers a large set of services to the real system.•Almost never a DT share the elaborated analysis to the real counterpart.•A DT application is proposed in a Simulink environment to overcome these gaps.•The illustrated DT poses the basis for further improvements. In the Industry 4.0 era, the Digital Twin (DT), virtual copies of the system that are able to interact with the physical counterparts in a bi-directional way, seem to be promising enablers to replicate production systems in real time and analyse them. A DT should be capable to guarantee well-defined services to support various activities such as monitoring, maintenance, management, optimization and safety. Through an analysis of the current picture of manufacturing and a literature review about the already existing DT environment, this paper identifies what is still missing in the implemented DT to be compliant to their description in literature. Particular focuses of this paper are the degree of integration of the proposed DT with the control of the physical system, in particular with the Manufacturing Execution Systems (MES) when the production system is based on the Automation Pyramid, and the services offered from these environments, comparing them to the reference ones. This paper proposes also a practical implementation of a DT in a MES equipped assembly laboratory line of the School of Management of the Politecnico di Milano. The application has been created to pose the basis to overcome the missing implementation aspects found in literature. In such a way, the developed DT paves the way for future research to close the loop between the MES and the DT taking into consideration the number of services that a DT could offer in a single environment.